Social Media and Democratic Consolidation in the Postmilitarized Nations: A Study of Pakistan, Nigeria and Brazil - Saiqa Sadiq; Rana Pervaiz Iqbal; Nayyer Sultana (Journal of Management Practices, Humanities and Social Sciences, 2024)
Over the past few decades, social media has developed a ubiquitous part of our global world mainly used for commerce, networking, and entertainment. However, over the last few years, there has been a rise in the use of social media in party-political debate and actions, especially in developed democracies and post-militarized countries. Is this to suggest that social media will have an effect on democratic transformation and consolidation in the twenty-first century? This paper aims to address this question by exploring the usage of social media as a potential democratic consolidation instrument in Pakistan, Nigeria, and Brazil. There is no denying that digital technologies and social media networks have dramatically improved human contact in the twenty-first century. Because of the partaking, collaborating, and moneymaking attributes of social media, they have become veritable tools for the strengthening of self governing principles and processes in terms of knowledge exchange, election tracking, and assessment, reduction of tensions and anxieties related to votes, and maintaining and even implementing transparency and answerability to a wide swath of the population. The paper, on the other hand, acknowledges that while social media has its own set of issues, such as the potential for violence and despoliation, these can be effectively mitigated, if not entirely eliminated, through adequate monitoring and regulatory controls deprived of jeopardizing the independence of speech. It thus contends that, despite the teething problems in each nation, the proper use of social media in fostering and maintaining participatory democracy in Pakistan, Nigeria, and Brazil in the twenty-first century has the potential to deepen and consolidate democracy in the respective countries.